2021
DOI: 10.18805/ajdfr.dr-219
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Antibacterial and Antioxidant Capacities of Fixed Oil of Moringa oleifera L. Cultivated in the Southwest of Algeria

Abstract: Background: Since time immemorial, humans have always been interested in lipids for various uses, namely food, cosmetology, medicine, etc. Many seeds, sources of oils, are increasingly studied for their nutritional and therapeutic properties. Methods: The present study aims to valorize the vegetable oil obtained from the seeds of the Moringa oleifera plant widely cultivated in the southwest of Algeria, using the solid-liquid extraction technique. In addition, the fatty acid analysis of this oil, using the gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Figure 1. Presentation of the MO leaves collection site (Boulal et al, 2021) Patients and ethical issues We recruited 44 diabetic volunteers from Adrar city, 1200 km south of Algeria. Diabetic patients were excluded if they had any major cardiac, respiratory, renal, liver or mental disease; or if they had any allergy to MO leaves powder.…”
Section: Collection and Preparation Of Plant Materialsmentioning
confidence: 99%
“…Figure 1. Presentation of the MO leaves collection site (Boulal et al, 2021) Patients and ethical issues We recruited 44 diabetic volunteers from Adrar city, 1200 km south of Algeria. Diabetic patients were excluded if they had any major cardiac, respiratory, renal, liver or mental disease; or if they had any allergy to MO leaves powder.…”
Section: Collection and Preparation Of Plant Materialsmentioning
confidence: 99%
“…The sample collection is carried out in the region of Mraguen, one of the ksours of the municipality of Adrar which is located north of the city of Adrar. The high acid number of date stone oil (IA = 8.97mg KOH / g of oil), low volatility and excessive amount of polyunsaturated free fatty acid (FFA) content caused unwanted formation soap [9,10]. Therefore, these decrease the yield of biodiesel during the transesterification process [11,12].…”
Section: Organic Materialsmentioning
confidence: 99%
“…This plant leaf is abundant in macronutrients (Protein rich, high carbohydrate content, dietary fibers), micronutrients (vitamin B complex, A, C and D) and phytochemicals (Ansari et al, 2020). Furthermore, it has been reported that the leaves of this plant have a number of biological properties, including diuretic, immune-stimulating, hypotensive, anti-inflammatory, anti-ulcer, anti-hepatotoxic, anti-tumor, thyroid hormone status regulation, hypocholesterolemic, radio protective, hypolipidaemic, anti-atherosclerotic, antidiabetic and antioxidant properties (Yadav and Ghimire, 2019;Boulal et al, 2021;Das et al, 2022). Addition of Moringa oleifera leaves powder (1.0-1.5% w/v) to yoghurt enhanced the nutritional profile of the yoghurt indicated by increased total solids, protein and fat content of the herbal yoghurt over the plain yoghurt (Akajiaku et al, 2018).…”
Section: Introductionmentioning
confidence: 99%